First record of Thomasomys cinereus Thomas, 1882 (Rodentia, Cricetidae, Sigmodontinae) in Ecuador - Moreno Cárdenas, Pablo A.; Novillo-Gonzalez, Marylin (THERYA, 2020)
The Andean forests of southwestern Ecuador and northern Peru, hold a unique assemblage of species, given the existence of high habitat diversity. Our aim is to characterize the small mammal diversity at Yacuri National Park in southern Ecuador. We collected small non-volant mammals, using Sherman, Pitfall, and Tomahawk traps, in wet and dry habitats in the Yacuri National Park; and obtained some specimens of rodents and marsupials in the pluviseasonal forest in southern Ecuador. We registered several non-volant small mammal species, including the first Ecuadorian record of the olive-gray mouse Thomasomys cinereus. This record expands the known species distribution, 10 km from the northernmost location in Peru within the same ecosystems.